Pelatihan Pembuatan Kompos Sebagai Pemanfaatan Sampah Organik Di Lingkungan Pondok Pesantren MaQis Al-Hamidy 4 - Adin Kurniawan; Antono Landjar Patoman; Wahyu Mukti Jaya Nata; Zulham Yahya; Rossyda Priyadarshini; Zainal Abidin Achmad (Universitas Muhammadiyah Manado, 2023)
Garbage is a residual material produced by a household. Waste can become a problem if it is not managed properly. MaQis Al-Hamidy 4 Islamic Boarding School is a boarding school that is well known among Madurese people. This Islamic boarding school has an environment where lots of trees grow, resulting in quite a lot of dry leaf waste. This of course provides both disadvantages and advantages for the residents of Islamic boarding schools. Therefore, it is necessary to conduct training for residents of Islamic boarding schools in the form of making compost from dry leaf waste so that it can provide benefits for residents of Islamic boarding schools and for the environment. The purpose of this training is to provide education about environmental management, especially in the utilization of organic waste which can be used as material for making compost. The method in implementing this training uses descriptive analysis as well as direct waste management practices. The result and impact of this training is that students gain useful skills in organic waste management and become agents of change in protecting the environment.